2017
DOI: 10.1002/chem.201700806
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of α,β‐Unsaturated Aldehydes and Ketones by Air‐Stable Ruthenium NNS Complexes

Abstract: The selective hydrogenation of the carbonyl functionality of α,β-unsaturated aldehydes and ketones is catalysed by ruthenium dichloride complexes bearing a tridentate NNS ligand as well as triphenylphosphine. The tridentate ligand backbone is flexible, as evidenced by the equilibrium observed in solution between the cis- and trans-isomers of the dichloride precatalysts, as well as crystal structures of several of these complexes. The complexes are activated by base in the presence of hydrogen and readily hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…1 H NMR (600 MHz, CDCl3) δ 8.09 (s, 1H), 8.04 (s, 1H), 2.99 (q, J = 7.4 Hz, 2H), 2.71 (s, 3H), 1.39 (t, J = 7.4 Hz, 3H). 13 5,6,7,8-tetrahydroquinoxaline (6u) 13 Colourless Oil (151mg, 72%) 1…”
Section: 7-dichloro-2-ethyl-3-methylquinoxaline (6t) 12mentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR (600 MHz, CDCl3) δ 8.09 (s, 1H), 8.04 (s, 1H), 2.99 (q, J = 7.4 Hz, 2H), 2.71 (s, 3H), 1.39 (t, J = 7.4 Hz, 3H). 13 5,6,7,8-tetrahydroquinoxaline (6u) 13 Colourless Oil (151mg, 72%) 1…”
Section: 7-dichloro-2-ethyl-3-methylquinoxaline (6t) 12mentioning
confidence: 99%
“…White solid (236 mg, 82%)1 H NMR (600 MHz, CDCl3) δ 7.40 -7.39 (m, 4H), 7.29 -7.27 (m, 6H), 3.08 -3.05 (m, 4H), 2.00 -1.98 (m, 4 H). 13 C NMR (150 MHz, CDCl3) δ 150.65, 149.65, 139.06, 129.73, 128.29, 128.22, 31.91, 22.91.…”
mentioning
confidence: 99%
“…Recently, we reported on the development of a class of ruthenium NNS‐pincer complexes which showed high selectivity in the hydrogenation of unsaturated aldehydes and ketones to the corresponding unsaturated alcohols . These findings encouraged us to employ complex C1 a (Scheme ) in the hydrogenation of methyl cinnamate ( 1 a ).…”
Section: Resultsmentioning
confidence: 99%
“…This can be useful in cases where conventional hydrolysis is not feasible. We previously reported that the RuNNS catalyst selectively hydrogenates the aldehyde functionality in methyl 4‐formylbenzoate in methanol . Indeed, when this reaction was performed in toluene, both aldehyde and ester were reduced (entry 7).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this catalyst system showed good activity in the hydrogenation of α,β-unsaturated aldehydes (2q). [34] We also tested the selectivity of this method in the hydrogenation of aldehyde group in the presence of other carbonyl groups and moderate to good selectivity was observed and products were obtained in satisfactory yields (2r-t). We also, checked the reduction of ketones and esters but no alcohol product was detected, demonstrating this catalyst group is selective for reduction of aldehyde group under our optimized conditions.…”
Section: The Catalytic Application Of Immobilized Iridium Nanopartimentioning
confidence: 99%